Clinical recommendations on penile reconstructive and prosthetic surgery: a consensus statement from the Asia-Pacific Society of Sexual Medicine. Issue 2 (11th April 2023) - Chung, Eric; Moon, Du-Geon; Hui, Jiang; Chang, Hong-Chiang; Hakim, Lukman; Nagao, Koichi; Tan, Ronny; Mak, Siu King; Tantiwongse, Kavirach; Lin, Haocheng; Mai, Dung Ba Tien; Nguyen, Quang; et al.
Abstract: Introduction: Penile reconstructive and prosthetic surgery remains a highly specialized field where potential complications can be devastating, and unrealistic patient expectations can often be difficult to manage. Furthermore, surgical practice can vary depending on locoregional expertise and sociocultural factors. Methods: The Asia Pacific Society of Sexual Medicine (APSSM) panel of experts reviewed contemporary evidence regarding penile reconstructive and prosthetic surgery with an emphasis on key issues relevant to the Asia-Pacific (AP) region and developed a consensus statement and set of clinical practice recommendations on behalf of the APSSM. The Medline and EMBASE databases were searched using the following terms: "penile prosthesis implant, " "Peyronie's disease, " "penile lengthening, " "penile augmentation, " "penile enlargement, " "buried penis, " "penile disorders, " "penile trauma, " "transgender, " and "penile reconstruction" between January 2001 and June 2022. A modified Delphi method was undertaken, and the panel evaluated, agreed, and provided consensus statements on clinically relevant penile reconstructive and prosthetic surgery, namely (1) penile prosthesis implantation, (2) Peyronie's disease, (3) penile trauma, (4) gender-affirming (phalloplasty) surgery, and (5) penile esthetic (length and/or girth enlargement) surgery. Main outcome measures: Outcomes were specific statements and clinical recommendations according to the Oxford Centre for Evidence-Based Medicine, and if clinical evidence is lacking, a consensus agreement is adopted. The panel provided statements on clinical aspects of surgical management in penile reconstructive and prosthetic surgery. Results: There is a variation in surgical algorithms in patients based on sociocultural characteristics and the availability of local resources. Performing preoperative counseling and obtaining adequate informed consent are paramount and should be conducted to discuss various treatment options, including the pros and cons of each surgical intervention. Patients should be provided with information regarding potential complications related to surgery, and strict adherence to safe surgical principles, preoperative optimization of medical comorbidities and stringent postoperative care are important to improve patient satisfaction rates. For complex patients, surgical intervention should ideally be referred and performed by expert high-volume surgeons to maximize clinical outcomes. Clinical implications: Due to the uneven distribution of surgical access and expertise across the AP region, development of relevant comprehensive surgical protocols and regular training programs is desirable. Strengths and Limitations: This consensus statement covers comprehensive penile reconstructive and prosthetic surgery topics and is endorsed by the APSSM. The variations in surgical algorithms and lack of sufficient high-level evidence in these areas could be stated as a limitation. Conclusion: This APSSM consensus statement provides clinical recommendations on the surgical management of various penile reconstructive and prosthetic surgeries. The APSSM advocates for surgeons in AP to individualize surgical options based on patient condition(s) and needs, surgeon expertise, and local resources.